(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Metallic nanofluidsare suspensions of metallic particles of nanometre size in base fluids. The combination of two kinds of metallic particles mixed at the same volume ratio is known as multi-metallic nanoparticles. These multiple metallic particles of nanometre size were suspended in deionized H2Ovia the use of ultrasonic vibratorsat varying volume fractions as well as variations in the ratios of metallic/metallic particles of nanometre size. In our study the dynamic viscosity, the nanofluid’s heat conductivities were determined for varying temperatures and volume fractions. The coefficient of thermal transmissionof the flowing nanofluid in the constant wall heat flux tube were determined experimentally in laminar condition. The results revealedhuge thermal transmission enhancement comparison to the base fluids. The pressure loses were illustrated for all nanofluids. The comparisons of the different metallic and multi-metallic types of the nanofluids were showed that Cu nanofluids have a greater coefficient ofthermal transmission compared with the Cu-Zn, Zn atequal volume fractions.